Factors Determining Rice Farm Households’ Adoption of Organic Farming in Taiwan - Min-Han Tsai; Yun-Cih Chang; Ting-Ya Yang; Yir-Hueih Luh (Agronomy, 2021)
The adoption of environmentally friendly farming practices, such as organic farming, is promoted as a promising option for meeting the sustainable development goals in Taiwan. Taking the paddy rice as an example, this study examines the determining factors of organic farming adoption with an emphasis on farm households’ socio-economic characteristics. Based on data drawn from the 2015 Census of Agriculture, Forestry, Fishery and Animal Husbandry, rice farm households’ adoption of organic farming is defined as allocating part of the farmland to rice plantation without using any chemical fertilizers and pesticides. In line with previous research, farm operators’ age, educational level and on-farm workdays are found to be significant determinants of organic farming adoption. Socio-economic characteristics of the farm household are also found to be relevant to the adoption decision. The results suggest that household-level human capital such as proportion of middle-aged or elder members, and proportion of members with college degree, have significantly positive effect on the adoption probability. Since organic farming is more labor-demanding than conventional farming, this study performs a further analysis to examine the differences in the determining factors between full-time and part-time households. Relative to the young operators, middle-aged operators in the full-time households are found to be less likely to adopt organic farming, whereas the elder operators in the part-time households have a higher adoption probability. Additionally, share of members with a college degree is found to be another significant driving factor of adoption, which is however only true for the part-time households. Exploring the diverse impacts of socio-economic factors for the two groups of households contributes to the extant literature by narrowing the gap in understanding the relation between farm management strategy and organic farming adoption.